PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR MUSIK ANSAMBEL PADA SISWA KELAS VII SMP MUHAMMADIYAH RAMBAH T.P 2013/2014 - Ermita Nasution (Indonesian Journal of Basic Education, 2018)
The study was conducted using the Classroom Action Research approach to the implementation process, the study was divided into 2 cycles, each cycle covering planning, implementing actions, observing, and reflecting. Data collection techniques in this study using observation techniques, performance, questionnaires and documentation. The results showed that the peer tutoring method was able to improve the learning outcomes of playing ensemble musical instruments. In this case the musical instrument used is a recorder and pianika. The peer tutoring method is able to streamline meeting time in the classroom compared to the classical method. Based on the results of the study it was suggested that the arts and culture teachers apply the peer tutoring method in music ensemble learning at school. Try to apply the peer tutor method in achieving the lesson objectives in other basic competencies